Holcosus festivus (Central American Whitptail Lizard): Nuptial gift - Chaves Acuña, Wagner Josue (2021)
Signaling the ability to provision limited re-sources to a mate's reproductive success should be favored by sexual selection. In many taxa, female mate choice is driven by courtship offerings in the form of nutritional items, commonly known as nuptial gifts where males present their partners with feeding gifts before, during, or after courtship and/or copulating. Such mating effort has been widely reported across invertebrate species, but it has been less reported among vertebrates, especially reptiles. Here, we report on a novel mating ritual in the lizard Holcosus festivus from a tropical lowland rainforest in Costa Rica.